Épistémologie sculpturale, extraction et volume d’être - Catherine Beaugrand; Albert Piette (Ateliers d'Anthropologie)
The authors offer an exercise in sculptural epistemology, by comparing various types of sculpture, giving a special place to The Age of Bronze, which Rodin saw as a specific experiment. In attempting this exercise, they present The Age of Bronze as a radical extraction, unlike reliefs and most sculptures in the round conceived in relation to a space. The notion of form, linked with that of volume of being, is used to clarify how Rodin’s sculpture corresponds to a human being. In such a sculpture in the round, the “supports” holding it upright are important. They help us think about how human beings “hold up”, how they remain stable, despite their movement.